Immune Response Visualized In Vivo by [18F]-FDG PET/CT after COVID-19 Vaccine - Romain-David Seban; Laurence Champion; Nicolas Deleval; Capucine Richard; Claire Provost (Diagnostics, 2021)
Worldwide deployment of COVID-19 vaccines is in progress. Recent immune activation following vaccination can sometimes be seen in fluorine-18-fluorodeoxyglucose positron emission tomography/computed tomography ([18F]-FDG PET/CT). As previously evidenced, FDG-avid axillary lymph node(s) are common in patients receiving vaccines against SARS-CoV-2, influenza virus, or human papillomavirus, and reflect a regional immune response. In addition, these findings may also be accompanied by an increased spleen glucose metabolism after the COVID-19 vaccine, which captures a systemic immune response. Hence, we provide here a clinical example demonstrating that immune response could be associated with increased glucose metabolism in lymphoid organs such as lymph nodes and the spleen, which are critical modulators of T cell immunity. We believe that it is of paramount importance that nuclear physicians should be able to recognize clinical and imaging features of such immune responses upon vaccination for COVID-19 and beyond.